A polyimide film and its preparation method and application

Through a multi-layer polyimide film preparation method, the polycondensation reaction and chemical imidation treatment of aromatic dianhydride and aromatic diamine are used to solve the problems of uneven solvent volatility and insufficient mechanical properties in the preparation of ultra-thick polyimide films, and the film preparation with high mechanical properties and low gas transmittance is achieved.

CN119039645BActive Publication Date: 2025-04-25PETROCHINA SHANGHAI ADVANCED MATERIALS RESEARCH INSTITUTE CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411548016.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-04-25
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

When preparing ultra-thick polyimide films, the prior art faces the "surface dryness" phenomenon caused by increased difficulty in controlling the film solvent content, poor mechanical properties, insufficient self-support, easy tear and uneven solvent volatility, which affects production stability and safety.

Method used

A polyimide film is prepared using a method of preparing a polycondensation using the first and second aromatic dianhydrides with the aromatic diamine to form a resin solution, and the initial A film layer is formed by casting and heating drying treatment. Subsequently, the chemical imidizing reagent and the molecular weight reinforcement agent are mixed with the second resin solution, and laminated-heating treatment is performed to form a composite adhesive film, and finally high-temperature heating and bidirectional stretching treatment are performed to obtain a polyimide film.

Benefits of technology

The high mechanical properties of the polyimide film, low linear thermal expansion coefficient, high pressure resistance and low gas transmittance are achieved, and the problems of uneven solvent volatility and insufficient mechanical properties are solved, and the stability and safety of production are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119039645B_ABST
    Figure CN119039645B_ABST
Patent Text Reader

Abstract

The present invention discloses a polyimide film and a preparation method and application thereof. The polyimide film has a thickness of greater than or equal to 250 μm and comprises a film layer A and at least one film layer B in contact with each other; the surface roughness Rz of the film layer A is less than or equal to 1.0 μm; the number of micropores with a size greater than 0.1 mm in the film layer B is less than or equal to 1 / ㎡, and the density of the film layer B is greater than or equal to 1.45 g / cm 3 , surface roughness Rz≥1.2μm. The polyimide film provided by the present invention has the characteristics of large thickness, small linear thermal expansion coefficient, high pressure resistance and low gas permeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polyimide film, in particular to a polyimide film and a preparation method and application thereof, belonging to the technical field of polyimide film manufacturing. Background Art

[0002] Ultra-thick polyimide films with a thickness greater than 100μm have excellent heat resistance and heat insulation properties, outstanding mechanical properties and insulation properties, good chemical stability, and excellent dielectric properties. They have been widely used in precursor films of high thermal conductivity artificial graphite films, substrate films, cover films, and reinforcement films for microelectronic circuits, high-temperature protective films for flexible copper-clad laminate processes, protective films for lithium-ion battery insulation systems, protective films for new energy vehicle water cooling systems, and insulating films for motors and special electrical appliances. In particular, in recent years, with the transformation of 3C electronic products to compact structures and efficient operations, and the development of new energy vehicles to higher safety and reliability, the market demand for ultra-thick polyimide films with a thickness greater than 100μm has continued to increase.

[0003] Polyimide is a "stubborn" polymer material that is difficult to dissolve and melt. The current industrialized polyimide film manufacturing technology mainly adopts a two-step method. First, aromatic dianhydride and aromatic diamine are used to prepare polyamic acid solution by polycondensation in a solvent, and then a film containing a certain amount of solvent is prepared by casting the polyamic acid solution or a film containing a certain amount of solvent is prepared by mixing polyamic acid with a dehydrating agent, a catalyst, etc., and then the film is stretched and treated at high temperature to obtain a polyimide film. With this manufacturing technology, as the thickness of the produced polyimide film increases, the solvent content of the film will also increase exponentially. The control and effective removal of the film solvent content in the process not only affects the performance of the final polyimide film, but is also directly related to the stability and safety of the process.

[0004] At present, the preparation method of polyimide film has the following technical difficulties:

[0005] 1. It is more difficult to control the uniformity of solvent volatilization in the thickness direction of the film. The solvent on the surface of the film is easy to volatilize to form a hard solidified layer, and the evaporation of the inner layer solvent is hindered, resulting in a "surface drying" phenomenon. The solvent cannot evaporate in time, resulting in poor mechanical properties and insufficient self-support of the film. It is easy to tear under tension, resulting in production interruptions or even production failures.

[0006] 2. The film containing a large amount of solvent is attached to a smooth endless steel belt to dry. Due to the rapid and large amount of volatilization of the solvent, the film is prone to shrinkage, resulting in a narrowing of the width that cannot reach the process width. When the film runs to the bottom of the endless steel belt, due to the exponential increase in the weight of the film, the film and the steel belt are not sufficiently bonded and will detach from the steel belt, making it impossible to produce the film.

[0007] 3. When the film enters the stretching process, higher processing temperature will cause the film to shrink more violently, and the film will easily fall out of the fixture; insufficient mechanical properties of the film will also cause the film to tear from the fixture and fall out of the fixture; the film that has fallen out of the fixture will gather in rolls, and a large amount of solvent will not evaporate in time, which will cause fire safety issues.

[0008] 4. In addition to the above engineering problems, the rapid evaporation of the internal solvent during the film drying process will also lead to an increase in hole defects, insufficient mechanical properties of the prepared ultra-thick polyimide film, and quality problems, which will ultimately lead to limited application of the produced ultra-thick polyimide film or even its inability to be used.

[0009] Therefore, the control of the solvent content of the intermediate film and the balance of mechanical properties in the production of ultra-thick polyimide films are key bottlenecks.

[0010] U.S. invention patent US20220152912A1 discloses a method for manufacturing a polyimide film with a thickness greater than 400μm. The above technical difficulties are circumvented by controlling the thickness and solvent content of the single-layer adhesive film and combining it with a lamination composite method. However, the equipment required for this method is relatively complex and the processing cost is high. In addition, the ultra-thick polyimide film produced can be expected to have obvious interlayer interfaces, which are prone to stratification under high temperature and stress. U.S. invention patent US20220152912A1 also describes a polyimide film with a thickness greater than 200μm. Production generally requires drying and removing solvents at a speed of less than 1m / min. The production efficiency is extremely low, the production cost is high, and it is impossible to produce polyimide films with a thickness greater than 400μm. Chinese invention patent CN109647683 discloses a method of preparing a polyimide film with a thickness of 50μm~135μm by spraying once or multiple times, which can effectively avoid the "surface drying" problem, but the process is relatively complicated, and the mechanical and thermal properties of the produced polyimide film are difficult to meet the application requirements of high-tech industries. Chinese invention patent CN108527745A discloses a specially designed drying device, which heats one side of the film and cools the other side to make the solvent of the film diffuse and volatilize evenly from one side to the other side, but this method easily causes the solvent to condense on the surface of the cooling chamber and drip back to the surface of the film to form streaks. Chinese patent CN217654241U discloses an anti-condensation temperature control and fire extinguishing system for polyimide film production, which can effectively solve the fire problem caused by the film detaching from the fixture and the aggregation of the film during high-temperature stretching, but does not involve a solution for regulating the solvent content of thick films and balancing mechanical properties. Chinese invention patents CN110423467B, CN101168598A, and CN113788478A all describe methods for manufacturing ultra-thick polyimide films, but do not explain specific solutions to the above technical problems. The thickness of the ultra-thick polyimide films described in the above patents is less than 250 μm, and the manufacturing technology of polyimide films with a thickness greater than 250 μm still needs to be developed.

[0011] Therefore, developing a method for preparing a polyimide film with a thickness greater than 250 μm has become a key research direction in this field. Summary of the invention

[0012] The invention provides a polyimide film, which has the characteristics of large thickness, small linear thermal expansion coefficient, high pressure resistance and low gas permeability.

[0013] The present invention also provides a method for preparing a polyimide film, which has the characteristics of being able to manufacture a composite polyimide film with more than two layers and reducing the number of hole defects inside the polyimide film.

[0014] The invention also provides a circuit board, which has the characteristic of high dimensional stability.

[0015] The present invention also provides a gas barrier composite film, which has the characteristic of high gas barrier property.

[0016] The invention also provides an insulating composite film, which has the characteristic of high insulation.

[0017] The present invention provides a polyimide film, wherein the polyimide film has a thickness greater than or equal to 250 μm and comprises a film layer A and at least one film layer B that are in contact with each other;

[0018] The surface roughness of the A film layer is Rz≤1.0 μm;

[0019] The number of micropores with a size greater than 0.1 mm in the B film layer is ≤ 1 / ㎡, and the density of the B film layer is ≥ 1.45 g / cm 3 , surface roughness Rz≥1.2μm.

[0020] The polyimide film as described above, wherein the linear thermal expansion coefficient of the polyimide film is 12ppm / °C to 35ppm / °C, the breakdown voltage is ≥30kV, and the H2 transmittance is ≤1.0×10 -15 mol·m / m 2 ·s·Pa, the glass transition temperature of the polyimide in the A film layer is 180°C~300°C.

[0021] The polyimide film as described above, wherein the thickness of the A film layer accounts for 20-50% of the total thickness of the polyimide film.

[0022] The present invention also provides a method for preparing a polyimide film, which can be used to prepare any of the above-mentioned polyimide films. The method comprises the following steps:

[0023] 1) mixing a first aromatic dianhydride, a first aromatic diamine, a low boiling point solvent, a high boiling point solvent, and a filler, and causing the first aromatic dianhydride and the first aromatic diamine to undergo a polycondensation reaction to obtain a first resin solution;

[0024] 2) mixing a second aromatic dianhydride, a second aromatic diamine, a high boiling point solvent, and a filler, and causing the second aromatic dianhydride and the second aromatic diamine to undergo a polycondensation reaction to obtain a second resin solution;

[0025] 3) performing a first heating and drying treatment on the solution film formed by casting the first resin solution to obtain an initial A film layer;

[0026] 4) mixing the second resin solution with a chemical imidization agent and a molecular weight reinforcing agent to obtain a second resin mixed solution; performing at least one lamination-heating treatment on the initial A film layer using the second resin mixed solution to obtain an initial composite adhesive film;

[0027] 5) performing at least one heating and drying treatment on the initial composite film to obtain an intermediate composite film;

[0028] 6) subjecting the intermediate composite film to high temperature heating and biaxial stretching treatment to obtain the polyimide film;

[0029] The treatment temperature of the first heating and drying treatment is 50°C to 120°C, and the treatment time is 2min to 10min;

[0030] The lamination-heating treatment includes attaching the second resin mixed solution to the surface direction of one side of the initial A film layer, and performing a heating treatment at a temperature of 60° C. to 150° C. for a time of 5 min to 15 min;

[0031] The heating and drying treatment of the initial composite film is performed at a temperature of 50°C to 180°C and a treatment time of 18min to 60min;

[0032] The first aromatic dianhydride is selected from at least one of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4-biphenyltetracarboxylic dianhydride, 4,4'-biphenyl ether dianhydride, 3,4,3',4'-triphenyl diether dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]malonic dianhydride, 2,2-diphenylpropane-3,4,3',4'-tetracarboxylic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-diphenyl sulfone tetracarboxylic dianhydride, and p-phenylene-bis(triphenyl)phthalate dianhydride;

[0033] The first aromatic diamine is selected from at least one of 4,4'-diaminodiphenyl ether, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminodiphenylmethane, 2,2-bis(4-aminophenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 2,4-diaminotoluene, and 1,3-bis(aminopropyl)tetramethyldisiloxane;

[0034] The second aromatic dianhydride is selected from at least one of pyromellitic dianhydride and 3,3,4,4'-biphenyltetracarboxylic dianhydride;

[0035] The second aromatic diamine is selected from at least one of 4,4'-diaminodiphenyl ether and 1,4-phenylenediamine;

[0036] The solid content of the first resin solution is 10%-50%;

[0037] The solid content of the second resin solution is 10%-35%;

[0038] The low boiling point solvent is selected from at least one of acetone, butanone, toluene, ethyl acetate, tetrahydrofuran and chloroform;

[0039] The high boiling point solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone;

[0040] The filler is selected from at least one of calcium carbonate, calcium phosphate, calcium pyrophosphate, calcium hydrogen phosphate, silicon carbide, carbon nanotubes, graphene, carbon black, silicon dioxide, and titanium dioxide;

[0041] The chemical imidization reagent includes a dehydrating agent, a catalyst, a solvent, and an auxiliary agent;

[0042] The dehydrating agent is selected from at least one of acetic anhydride, trifluoroacetic anhydride, benzoic anhydride, acetyl chloride and thionyl chloride;

[0043] The catalyst is selected from at least one of quinoline, isoquinoline, pyridine, 3-methylpyridine, triethylamine, and N-methylimidazole;

[0044] The solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone;

[0045] The auxiliary agent is selected from at least one of tricresyl phosphate, triphenyl phosphate, toluene diphenyl phosphate, and trioctyl trimellitate;

[0046] The molecular weight reinforcing agent includes at least one of 1,2,4,5-pyromellitic acid, 3,3',4,4'-biphenyltetracarboxylic acid, tetrahydrofuran-2,3,4,5-tetracarboxylic acid, cyclohexane-1,2,4,5-tetracarboxylic acid, 1,2,3,4-cyclobutanetetracarboxylic acid, terephthalic acid, isophthalic acid, and terephthaloyl chloride;

[0047] The heating temperature of the high temperature heating and biaxial stretching treatment in step 6) is 150°C to 600°C;

[0048] The molecular weight reinforcing agent further comprises at least one of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone.

[0049] The preparation method as described above, wherein in step 1), the molar ratio of the first aromatic dianhydride to the first aromatic diamine is 0.99:1 to 1.05:1; and / or,

[0050] The molar ratio of the second aromatic dianhydride to the second aromatic diamine is 0.8:1 to 0.995:1.

[0051] The preparation method as described above, wherein the solid content of the first resin solution is 30%-40%; and / or,

[0052] The solid content of the second resin solution is 25%-35%.

[0053] The preparation method as described above, wherein the mass of the chemical imidization agent is 1%-30% of the mass of the second resin solution; and / or,

[0054] The molar ratio of the dehydrating agent to the catalyst in the chemical imidization reagent is 1:2-5:1; the mass fraction of the solvent is 10%-40%; the mass fraction of the auxiliary agent is 1%-10%; and / or,

[0055] The added amount of the filler is 0.05% to 5% of the sum of the mass of the aromatic diamine and the aromatic dianhydride.

[0056] In the preparation method as described above, the amount of the molecular weight reinforcing agent is equal to the difference between the amounts of the second aromatic diamine and the second aromatic dianhydride.

[0057] In the preparation method as described above, in step 5), the heating and drying treatment includes heating the upper surface and the lower surface of the initial composite film respectively, wherein the upper surface heating temperature is 50°C to 150°C, and the lower surface heating temperature is 80°C to 180°C.

[0058] The preparation method as described above, wherein in step 5), the heating and drying treatment of the initial composite adhesive film includes a second heating and drying treatment, a third heating and drying treatment, a fourth heating and drying treatment, a fifth heating and drying treatment, and a sixth heating and drying treatment performed in sequence;

[0059] The upper surface heating temperature of the second heating and drying treatment is 80°C to 120°C, the lower surface heating temperature is 120°C to 150°C, and the treatment time is 5min to 15min;

[0060] The third heating and drying treatment has an upper surface heating temperature of 90°C to 135°C, a lower surface heating temperature of 135°C to 180°C, and a treatment time of 1min to 8min;

[0061] The fourth heating and drying treatment has an upper surface heating temperature of 80°C to 120°C, a lower surface heating temperature of 120°C to 150°C, and a treatment time of 5min to 15min;

[0062] The fifth heating and drying treatment has an upper surface heating temperature of 60°C to 120°C, a lower surface heating temperature of 120°C to 150°C, and a treatment time of 5min to 15min;

[0063] The upper surface heating temperature of the sixth heating and drying treatment is 50°C to 100°C, the lower surface heating temperature is 100°C to 120°C, and the treatment time is 2min to 10min.

[0064] The preparation method as described above, wherein, in the lamination-heating treatment, the upper surface heating temperature of the heating treatment is 60°C to 120°C, and the lower surface heating temperature is 120°C to 180°C.

[0065] The present invention also provides a circuit board, wherein the circuit board comprises any one of the above-mentioned polyimide films.

[0066] The present invention also provides a gas barrier composite film, wherein the gas barrier composite film comprises any one of the above-mentioned polyimide films.

[0067] The present invention also provides an insulating composite film, wherein the insulating composite film comprises any one of the above-mentioned polyimide films.

[0068] The polyimide film provided by the invention has the characteristics of large thickness, small linear thermal expansion coefficient, high pressure resistance and low gas permeability. BRIEF DESCRIPTION OF THE DRAWINGS

[0069] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced one by one below. Obviously, the drawings in the following description are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0070] Figure 1 This is a structural diagram of a polyimide film production device.

[0071] Description of reference numerals:

[0072] 101-first extrusion die head;

[0073] 102-second extrusion die head;

[0074] 103- mixer;

[0075] 104-a first heating driving roller;

[0076] 105-a first heated driven roller;

[0077] 106 - second heated driven roller;

[0078] 107-third heating driven roller;

[0079] 108- fourth heating driven roller;

[0080] 109-fifth heating driven roller;

[0081] 110-sixth heating driven roller;

[0082] 111 - a second heating driving roller;

[0083] A-first drying zone;

[0084] B-second drying zone;

[0085] C-third drying zone;

[0086] D-fourth drying zone;

[0087] E-fifth drying zone;

[0088] F-sixth drying zone;

[0089] G-Seventh drying zone. DETAILED DESCRIPTION

[0090] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0091] A first aspect of the present invention provides a polyimide film having a thickness greater than or equal to 250 μm, comprising a film layer A and at least one film layer B in contact with each other;

[0092] The surface roughness of the A film layer is Rz≤1.0μm;

[0093] The number of micropores larger than 0.1 mm in the B film layer is ≤ 1 / ㎡, and the density of the B film layer is ≥ 1.45 g / cm 3 , surface roughness Rz≥1.2μm.

[0094] The polyimide film provided by the present invention is a multilayer film with a total thickness greater than or equal to 250 μm and a number of layers greater than or equal to two. This multilayer film includes two components, the first component constitutes the A film layer, and the second component constitutes the B film layer. Among them, the A film layer has one layer, which is located on one side surface of the polyimide film, the B film layer has one or more layers, and the A film layer and the B film layer are fused and contacted with each other in a stacked manner. Therefore, in one embodiment, when the polyimide film has a two-layer structure, from bottom to top, they are: A film layer, B film layer; when the polyimide film has a three-layer structure, from bottom to top, they are: A film layer, first B film layer, second B film layer. The B film layer is the main component of the composite film, and the A film layer is a functional layer that assists in the manufacture of the B film layer. When the A film layer is formed, it is located between the support member (for example, a steel belt) and the B film layer, and the surface roughness after forming is relatively small (surface roughness Rz ≤ 1.0 μm); the B film layer is located above the A film layer and in contact with the air, and the surface roughness after forming is relatively large (surface roughness Rz ≥ 1.2 μm). In the polyimide film provided by the present invention, the number of micropores in the B film layer with a size greater than 0.1 mm is ≤ 1 / ㎡, and the density of the B film layer is ≥ 1.45 g / cm 3 .

[0095] The polyimide film provided by the present invention has the characteristics of large thickness, low thermal expansion coefficient, high breakdown voltage and low gas permeability.

[0096] Furthermore, the linear thermal expansion coefficient of the polyimide film provided by the present invention is between 12ppm / ℃ and 35ppm / ℃, the breakdown voltage is ≥30kV, and the H2 transmittance is ≤1.0×10 -15 mol·m / m 2·s·Pa, the glass transition temperature of film layer A is 180℃~300℃.

[0097] In one embodiment, the thickness of the A film layer accounts for 20%-50% of the total thickness of the polyimide film. The polyimide film meeting the above thickness percentage has more prominent characteristics of small linear thermal expansion coefficient, high breakdown voltage and low gas permeability.

[0098] The second aspect of the present invention provides a method for preparing a polyimide film, which can be used to prepare the polyimide film provided by the first aspect of the present invention. The method comprises the following steps:

[0099] 1) mixing a first aromatic dianhydride, a first aromatic diamine, a low boiling point solvent, a high boiling point solvent, and a filler, and causing the first aromatic dianhydride and the first aromatic diamine to undergo a polycondensation reaction to obtain a first resin solution;

[0100] 2) mixing a second aromatic dianhydride, a second aromatic diamine, a high boiling point solvent, and a filler to allow the second aromatic dianhydride and the second aromatic diamine to undergo a polycondensation reaction to obtain a second resin solution;

[0101] 3) performing a first heating and drying treatment on the solution film formed by casting the first resin solution to obtain an initial A film layer;

[0102] 4) mixing the second resin solution with a chemical imidization agent and a molecular weight reinforcing agent to obtain a second resin mixed solution; performing at least one lamination-heating treatment on the initial A film layer using the second resin mixed solution to obtain an initial composite adhesive film;

[0103] 5) performing at least one heating and drying treatment on the initial composite film to obtain an intermediate composite film;

[0104] 6) The intermediate composite film is subjected to high temperature heating and biaxial stretching treatment to obtain a polyimide film;

[0105] The first heating and drying treatment has a treatment temperature of 50-120°C and a treatment time of 2-10 minutes;

[0106] The lamination-heating treatment includes attaching a second resin mixed solution to one side surface of the initial A film layer, and performing a heating treatment at a temperature of 60° C. to 150° C. for 5 min to 15 min;

[0107] The heating and drying treatment temperature of the initial composite film is 50℃~180℃, and the treatment time is 18min~60min;

[0108] The first aromatic dianhydride is selected from at least one of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4-biphenyltetracarboxylic dianhydride, 4,4'-biphenyl ether dianhydride, 3,4,3',4'-triphenyl diether dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]malonic dianhydride, 2,2-diphenylpropane-3,4,3',4'-tetracarboxylic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-diphenyl sulfone tetracarboxylic dianhydride, and p-phenylene-bis(triphenyl)phthalate dianhydride;

[0109] The first aromatic diamine is selected from at least one of 4,4'-diaminodiphenyl ether, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminodiphenylmethane, 2,2-bis(4-aminophenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 2,4-diaminotoluene, and 1,3-bis(aminopropane)tetramethyldisiloxane;

[0110] The second aromatic dianhydride is selected from at least one of pyromellitic dianhydride and 3,3,4,4'-biphenyltetracarboxylic dianhydride;

[0111] The second aromatic diamine is selected from at least one of 4,4'-diaminodiphenyl ether and 1,4-phenylenediamine;

[0112] The solid content of the first resin solution is 10%-50%;

[0113] The solid content of the second resin solution is 10%-35%;

[0114] The low boiling point solvent is selected from at least one of acetone, butanone, toluene, ethyl acetate, tetrahydrofuran and chloroform;

[0115] The high boiling point solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone;

[0116] The filler is selected from at least one of calcium carbonate, calcium phosphate, calcium pyrophosphate, calcium hydrogen phosphate, silicon carbide, carbon nanotubes, graphene, carbon black, silicon dioxide, and titanium dioxide;

[0117] Chemical imidization reagents include dehydrating agents, catalysts, imidization solvents, and auxiliary agents;

[0118] The dehydrating agent is selected from at least one of acetic anhydride, trifluoroacetic anhydride, benzoic anhydride, acetyl chloride and thionyl chloride;

[0119] The catalyst is selected from at least one of quinoline, isoquinoline, pyridine, 3-methylpyridine, triethylamine, and N-methylimidazole;

[0120] The imidization solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone;

[0121] The auxiliary agent is selected from at least one of tricresyl phosphate, triphenyl phosphate, toluene diphenyl phosphate, and trioctyl trimellitate;

[0122] The molecular weight reinforcing agent includes at least one of 1,2,4,5-pyromellitic acid, 3,3',4,4'-biphenyltetracarboxylic acid, tetrahydrofuran-2,3,4,5-tetracarboxylic acid, cyclohexane-1,2,4,5-tetracarboxylic acid, 1,2,3,4-cyclobutanetetracarboxylic acid, terephthalic acid, isophthalic acid, and terephthaloyl chloride; the heating temperature of the high temperature heating and biaxial stretching treatment in step 6) is 150°C to 600°C.

[0123] Specifically, in step 1), the first aromatic dianhydride and the first aromatic diamine are used for polycondensation reaction. The present invention does not limit the number of types of the first aromatic dianhydride and the first aromatic diamine, and one or more types of the first aromatic dianhydride and the first aromatic diamine can be selected.

[0124] The low boiling point solvent is a solvent with a boiling point range of 55°C to 120°C, selected from at least one of acetone, butanone, toluene, ethyl acetate, tetrahydrofuran, and chloroform; the high boiling point solvent is a solvent with a boiling point range of 150°C to 230°C, selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone. The low boiling point solvent and the high boiling point solvent are combined to obtain a solvent that is easy to remove during the heating and drying process, which can achieve the design purpose of controlling the total amount of solvent volatilization from the front end of the coating, greatly reduce the shrinkage size of the film caused by solvent volatilization, and reduce the occurrence of the "surface drying" phenomenon (that is, during the heating and drying process, the surface layer of the object to be treated dries before the inner layer, resulting in the phenomenon that the inner layer solvent is difficult to volatilize).

[0125] The present invention does not limit the ratio of the low boiling point solvent to the high boiling point solvent. In one embodiment, the mass ratio of the low boiling point solvent to the high boiling point solvent is 20:100 to 40:100.

[0126] Chemical imidization reagents can realize the conversion of polyamic acid into polyimide at low temperature. Chemical imidization reagents include dehydrating agents, catalysts, imidization solvents, and additives.

[0127] Among them, the dehydrating agent is selected from at least one of acetic anhydride, trifluoroacetic anhydride, benzoic anhydride, acetyl chloride, and thionyl chloride; the catalyst is selected from at least one of quinoline, isoquinoline, pyridine, 3-methylpyridine, triethylamine, and N-methylimidazole; the imidization solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; the auxiliary agent is selected from at least one of tricresyl phosphate, triphenyl phosphate, toluene diphenyl phosphate, and trioctyl trimellitate; the molecular weight reinforcing agent includes at least one of 1,2,4,5-pyromellitic acid, 3,3',4,4'-biphenyltetracarboxylic acid, tetrahydrofuran-2,3,4,5-tetracarboxylic acid, cyclohexane-1,2,4,5-tetracarboxylic acid, 1,2,3,4-cyclobutanetetracarboxylic acid, terephthalic acid, isophthalic acid, and terephthaloyl chloride. The molecular weight reinforcing agent is soluble in a solvent, and the solvent may be selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

[0128] The present invention does not limit the ratio of the dehydrating agent, the catalyst, the solvent and the auxiliary agent. In one embodiment, the mass ratio of the dehydrating agent, the catalyst, the solvent and the auxiliary agent is 1099:501:400:100.

[0129] Furthermore, the role of the filler is to improve the opening performance of the polyimide film, and can play an anti-static and anti-adhesion technical effect. The function of the molecular weight reinforcing agent is to extend the chain of the polyimide molecules during the production process of the polyimide film and increase the molecular weight of the polyimide.

[0130] The present invention does not limit the specific implementation method of step 1), as long as the requirement that the first aromatic dianhydride and the first aromatic diamine can undergo polycondensation to obtain the first resin solution can be met. Specifically, in step 1), any of the following methods can be used to prepare the first resin solution:

[0131] a) Under the protection of inert gas, add a low boiling point solvent and a high boiling point solvent to the reactor in sequence; start stirring; add a filler to the reactor and stir; slowly add the first aromatic diamine to the reactor and stir and dissolve it; slowly add the first aromatic dianhydride to the reactor; polymerize the first aromatic dianhydride and the first aromatic diamine for a period of time to obtain a first resin solution; and store it in a frozen state at a low temperature. In the solution, the resin molecular structure is a polymer of a first aromatic diamine and a first aromatic dianhydride.

[0132] b) Under the protection of inert gas, add low boiling point solvent and high boiling point solvent to the reactor in sequence; start stirring; add filler to the reactor and stir; slowly add the first first aromatic diamine to the reactor and stir; slowly add the first first aromatic dianhydride to the reactor; carry out the first polymerization, after a period of reaction, slowly add the second first aromatic dianhydride to the reactor, carry out the second polymerization, add the third and above first aromatic dianhydrides according to the adding method of the second first aromatic dianhydride and react, finally obtain the first resin solution; store it in cold storage at low temperature; in the solution, the resin molecular structure is a random copolymer of one first aromatic diamine and two or more first aromatic dianhydrides.

[0133] c) Under the protection of inert gas, add low boiling point solvent and high boiling point solvent to the reactor in sequence; start stirring; add filler to the reactor and stir; slowly add the first first aromatic diamine to the reactor and stir; slowly add the first first aromatic dianhydride to the reactor; carry out the first polymerization, after a period of reaction, slowly add the second first aromatic diamine to the reactor and carry out the second polymerization; after a period of reaction, slowly add the second first aromatic dianhydride to the reactor and carry out the third polymerization; after a period of reaction, obtain the first resin solution; freeze and store at low temperature. In the solution, the resin molecular structure is a block copolymer of two first aromatic diamines and two first aromatic dianhydrides; block copolymers of two or more first aromatic diamines and two or more first aromatic dianhydrides can be carried out according to this method.

[0134] d) Under the protection of inert gas, add a low boiling point solvent and a high boiling point solvent into the reactor; start stirring; add a filler into the reactor and stir; slowly add two or more first aromatic diamines into the reactor and stir; slowly add one first aromatic dianhydride into the reactor; carry out polymerization reaction for a period of time to obtain a first resin solution; store it in a frozen state at low temperature; in the solution, the resin molecular structure is a random copolymer of one first aromatic dianhydride and two or more first aromatic diamines.

[0135] e) Under the protection of inert gas, add a low boiling point solvent and a high boiling point solvent to the reactor; start stirring; add a filler to the reactor and stir; slowly add the first first aromatic diamine to the reactor and stir; slowly add the first first aromatic dianhydride to the reactor; carry out the first polymerization, and after a period of reaction, slowly add the second first aromatic diamine to the reactor to carry out the second polymerization, and the third and more first aromatic diamines are added and reacted according to the addition method of the second first aromatic diamine to finally obtain a first resin solution; freeze and store at low temperature; in the solution, the resin molecular structure is a block copolymer of one first aromatic dianhydride and two or more first aromatic diamines.

[0136] That is, the first resin solution includes but is not limited to: a block copolymer or random copolymer of one first aromatic dianhydride and one first aromatic diamine or two or more first aromatic diamines; a block copolymer or random copolymer of one first aromatic diamine and one first aromatic dianhydride or two or more first aromatic dianhydrides; a block copolymer or random copolymer of two or more first aromatic dianhydrides and two or more first aromatic diamines.

[0137] In step 2), the second aromatic dianhydride and the second aromatic diamine are used for polycondensation reaction. The present invention does not limit the number of types of the second aromatic dianhydride and the second aromatic diamine, and one or more types of the second aromatic dianhydride and the second aromatic diamine can be selected.

[0138] The present invention does not limit the specific implementation method of step 2), as long as the second aromatic dianhydride and the second aromatic diamine can undergo polycondensation to obtain the second resin solution. Specifically, the second resin solution can be prepared in step 2 using the same method as step 1).

[0139] The second resin solution includes but is not limited to a block copolymer or random copolymer of one second aromatic dianhydride and one second aromatic diamine or two second aromatic diamines, a block copolymer or random copolymer of one second aromatic diamine and one second aromatic dianhydride or two second aromatic dianhydrides, and a block copolymer or random copolymer of two second aromatic dianhydrides and two second aromatic diamines.

[0140] Furthermore, in step 3), the solution film formed by casting the first resin solution is subjected to a first heating and drying treatment to obtain an initial A film layer. During the first heating and drying treatment, the solvent in the first resin solution volatilizes at a high temperature, and other components in the first resin solution form a solid initial A film layer. The treatment temperature of the first heating and drying treatment is 50°C to 120°C, and the treatment time is 2min to 10min. The above treatment conditions can volatilize the solvent in the solution film formed by casting the first resin solution at an appropriate rate to form an initial A film layer.

[0141] It is understandable that, in order to facilitate the drying of the solution film formed by casting the first resin solution, in one embodiment, the first resin solution can be extruded and cast onto a support member in a suitable form, and then the first resin solution extruded on the support member is subjected to a first heating and drying treatment to obtain an initial film layer A. The present invention does not limit the specific structure of the support member, and it can support the extruded cast resin solution. In one embodiment, the support member is a steel belt.

[0142] Furthermore, in one embodiment, the first heating and drying treatment heats the upper surface and the lower surface of the extruded first resin solution respectively, and the upper surface heating temperature is 80°C, and the lower surface heating temperature is 100°C. The upper surface refers to the side surface of the extruded first resin solution that is not in contact with the support member, and the lower surface refers to the side surface of the extruded first resin solution that is in contact with the support member. Using different heating methods on the upper surface and the lower surface of the extruded first resin solution can guide the organic volatiles in the film to evaporate vertically and evenly from one side of the support member, which can effectively regulate the solvent content in the film and avoid the technical effect of the "surface drying" problem.

[0143] Furthermore, in step 4), the initial A film layer of the second resin mixed solution obtained by mixing the second resin solution with the chemical imidization agent and the molecular weight reinforcement agent is subjected to at least one lamination-heating treatment to obtain an initial composite adhesive film. Specifically, the lamination-heating treatment includes attaching the second resin mixed solution to the surface direction of one side of the initial A film layer, and performing a heating treatment at a temperature of 60°C to 150°C for 5min to 15min, so that the organic volatiles in the second resin mixed solution in contact with the upper surface of the initial A film layer slowly evaporate and form a film, and at the same time, the chemical imidization agent and the molecular weight reinforcement agent included in the second resin mixed solution react with the second resin solution, so that the film layer formed by the second resin mixed solution has higher mechanical strength.

[0144] Thus, the above treatment finally obtains an initial composite adhesive film, which includes an initial A film layer and a film layer formed by drying the second resin mixed solution.

[0145] Furthermore, the above-mentioned lamination-heating treatment can be performed multiple times, that is, in the first lamination-heating treatment, the second resin mixed solution is extruded onto the upper surface of the initial A film layer and then heated to form a film (called a newly formed film), and then the second resin mixed solution is extruded again onto the surface of the above-mentioned newly formed film that is away from the initial A film layer and then heated, so as to form an initial composite adhesive film with a three-layer structure.

[0146] The present invention does not limit the specific number of times the lamination-heating treatment is performed, and the specific number of times can be determined according to the number of layers of the initial composite adhesive film to be obtained, and the specific number of times is one less than the number of layers of the initial composite adhesive film to be obtained. For example, if the number of layers of the initial composite adhesive film to be obtained is 2, the specific number of times the lamination-heating treatment is performed is 1; if the number of layers of the initial composite adhesive film to be obtained is 3, the specific number of times the lamination-heating treatment is performed is 2. And so on.

[0147] Furthermore, the initial composite film is subjected to at least one heating and drying treatment in sequence to obtain an intermediate composite film. During the heating and drying process, the solvent contained in the initial composite film continues to volatilize, and the chemical imidization agent, the molecular weight reinforcing agent and other components contained in the second resin solution continue to react to obtain an intermediate composite film, and the intermediate composite film is subjected to a biaxial stretching treatment (including a transverse stretching treatment and a longitudinal stretching treatment) to obtain the polyimide film provided by the present invention.

[0148] The treatment temperature of each heating and drying treatment is 50° C.-180° C., and the treatment time is 18 min-60 min. The present invention does not limit the specific number of treatments of the heating and drying treatment, which can be determined according to needs.

[0149] Furthermore, the solid content of the first resin solution is 10%-50%, and the solid content of the second resin solution is 10%-35%. The solid content of the first resin solution refers to the ratio of the total mass of the first aromatic dianhydride, the first aromatic diamine, and the filler to the mass of the first resin solution, and the solid content of the second resin solution refers to the ratio of the total mass of the second aromatic dianhydride, the second aromatic diamine, and the filler to the mass of the second resin solution.

[0150] The first resin solution has the characteristic of high adhesion. The initial A film layer prepared by cast drying is located at the bottom layer and is in direct contact with the supporting part. It can not only greatly improve the adhesion with the supporting part, but also stably support the weight of the subsequent laminated film, effectively solving the problem of tape debonding caused by insufficient adhesion between the ultra-thick film and the supporting part.

[0151] The second resin solution is used to prepare the adhesive film, which is located above the initial A film layer and is not in direct contact with the supporting part, thereby avoiding the shrinkage and debonding problems caused by insufficient bonding with the supporting part. The second resin solution reacts with the chemical imidization agent and combines with the effect of the molecular weight reinforcement agent to prepare an adhesive film with high mechanical properties, thereby solving the tearing problem caused by insufficient mechanical properties during the film production process.

[0152] Furthermore, both the first resin solution and the second resin solution have a high solid content, which can control the initial organic volatiles of the cast film to a lower mass percentage and significantly reduce the evaporation amount of the organic volatiles per unit time. This not only helps to control the shrinkage size of the film and avoid the problem of tape debonding, but also helps to reduce the number of pore defects inside the film caused by the evaporation of organic volatiles, and prepare an intermediate film with controllable solvent content and high mechanical properties, thereby increasing the density of the polyimide film and reducing the linear thermal expansion coefficient and gas permeability of the polyimide film.

[0153] The first resin solution and the second resin solution used in the preparation method of the polyimide film provided by the present invention both have the characteristics of high solid content. Among them, the first resin solution contains both a high boiling point solvent and a low boiling point solvent, so that the solvent is easy to remove during the heating and drying process, which can reduce the solvent content of the inner layer of the film, not only can reduce the "surface drying" phenomenon, but also can reduce the shrinkage size of the support layer film during the drying process, and prevent the tape from falling off;

[0154] Furthermore, the first resin solution also has the characteristic of high adhesion. The initial A film layer prepared by the first heating and drying treatment is located at the bottom layer and is in direct contact with the supporting member. It can not only greatly improve the adhesion with the supporting member, but also stably support the weight of the subsequent laminated film, and effectively solve the problem of tape debonding caused by insufficient adhesion between the ultra-thick film and the steel belt; further, the second layer and above of the film prepared by the second resin solution is located above the initial A film layer, and is not in direct contact with the supporting member, thereby avoiding shrinkage and tape debonding problems caused by insufficient adhesion with the supporting member. The second resin solution reacts with the chemical imidization agent and combines the effect of the molecular weight reinforcement agent to prepare a film with high mechanical properties, and can also solve the tearing problem caused by insufficient mechanical properties during the film production process.

[0155] In one embodiment, the heating temperature of the high temperature heating and biaxial stretching treatment in step 6) can be controlled to be 150° C. to 600° C. The above treatment conditions can make the intermediate composite film more uniformly stretched to obtain a polyimide film.

[0156] In one embodiment, in step 1), the molar ratio of the first aromatic dianhydride to the first aromatic diamine is 0.99:1 to 1.05:1, and in a preferred embodiment, the molar ratio of the first aromatic dianhydride to the first aromatic diamine is 0.995:1 to 1.02:1; further, the molar ratio of the second aromatic dianhydride to the second aromatic diamine is 0.8:1 to 0.995:1, and in a preferred embodiment, the molar ratio of the second aromatic dianhydride to the second aromatic diamine is 0.88:1 to 0.98:1. Controlling the aromatic dianhydride and the aromatic diamine to meet the above molar ratio for polycondensation reaction can accurately synthesize a polyamic acid resin solution of a certain viscosity.

[0157] Furthermore, in one embodiment, the solid content of the first resin solution is 30%-40%; further, the solid content of the second resin solution is 25%-35%. The high solid content characteristics of the first resin solution and the second resin solution can control the total amount of organic volatiles from the coating front end, greatly reduce the shrinkage size of the film caused by solvent volatilization, and alleviate the "surface drying" phenomenon, which can not only achieve the stable preparation of the intermediate composite film, but also help to obtain a high-quality polyimide film with fewer internal "hole" defects.

[0158] In one embodiment, the mass of the chemical imidization agent is 1%-30% of the mass of the second resin solution, and in a preferred embodiment, the mass of the chemical imidization agent is 5%-15% of the mass of the second resin solution; further, the molar ratio of the dehydrating agent to the catalyst in the chemical imidization agent is 1:2~5:1, and in a preferred embodiment, it is preferably 2:1; the mass fraction of the solvent is 10%~40%, and in a preferred embodiment, it is preferably 20%; the mass fraction of the auxiliary agent is 1%~10%, and in a preferred embodiment, it is preferably 5%; further, the mass of the filler is 0.05%~5% of the sum of the mass of the aromatic diamine and the aromatic dianhydride, preferably 0.1%. The addition amount of the above-mentioned chemical imidization agent can convert the polyamic acid into polyimide at low temperature through the chemical imidization method, and the prepared polyimide film has the advantages of high tensile strength and small linear thermal expansion coefficient.

[0159] Furthermore, in one embodiment, the amount of the molecular weight reinforcing agent is equal to the difference between the amounts of the second aromatic diamine and the second aromatic dianhydride. When the amount of the molecular weight reinforcing agent meets the above conditions, the mechanical properties of the prepared polyimide film can be improved by increasing the molecular weight of the polyimide.

[0160] In one embodiment, in step 5), the heating and drying treatment includes heating the upper surface and the lower surface of the initial composite film separately, wherein the heating temperature of the upper surface is 50°C to 150°C, and the heating temperature of the lower surface is 80°C to 180°C. The upper surface refers to the surface of the initial composite film that has been subjected to the lamination-heating treatment. The lower surface refers to the surface of the initial composite film that has not been subjected to the lamination-heating treatment, that is, the surface in contact with the supporting member. Heating the upper surface and the lower surface of the initial composite film separately can guide the organic volatiles in the film to evaporate vertically and evenly from one side of the supporting member to the outside, which can effectively regulate the solvent content in the film and avoid the problem of "surface drying".

[0161] Further, in one embodiment, in step 5), the heating and drying treatment of the initial composite adhesive film includes a second heating and drying treatment, a third heating and drying treatment, a fourth heating and drying treatment, a fifth heating and drying treatment, and a sixth heating and drying treatment performed in sequence;

[0162] The upper surface heating temperature of the second heating and drying treatment is 80°C to 120°C, the lower surface heating temperature is 120°C to 150°C, and the treatment time is 5min to 15min;

[0163] The third heating and drying treatment is performed at an upper surface heating temperature of 90°C to 135°C, a lower surface heating temperature of 135°C to 180°C, and a treatment time of 1min to 8min.

[0164] The upper surface heating temperature of the fourth heating and drying treatment is 80°C to 120°C, the lower surface heating temperature is 120°C to 150°C, and the treatment time is 5min to 15min;

[0165] The upper surface heating temperature of the fifth heating and drying treatment is 60°C to 120°C, the lower surface heating temperature is 120°C to 150°C, and the treatment time is 5min to 15min;

[0166] The upper surface heating temperature of the sixth heating and drying treatment is 50°C to 100°C, the lower surface heating temperature is 100°C to 120°C, and the treatment time is 2min to 10min.

[0167] Heating the upper and lower surfaces of the initial composite film under the above conditions can guide the organic volatiles in the film to evaporate vertically and evenly from one side of the support, which can effectively control the solvent content in the film and avoid the "surface drying" problem.

[0168] Furthermore, in one embodiment, during the lamination-heating treatment, the upper surface heating temperature of the heating treatment is 60°C to 120°C, and the lower surface heating temperature is 120°C to 180°C. The lower surface is the surface on the side where the initial A film layer contacts the support, and the upper surface is the surface on the side where the second resin mixed solution is loaded. The above treatment conditions can guide the organic volatiles in the film to evaporate vertically and evenly from one side of the support, which can effectively regulate the solvent content in the film and avoid the "surface drying" problem.

[0169] The third aspect of the present invention provides a circuit board, which includes the polyimide film provided by the first aspect of the present invention. Further, in one embodiment, the circuit board is a flexible circuit board, and the polyimide film provided by the first aspect of the present invention is used as a substrate of the flexible circuit board. Since the polyimide film provided by the first aspect of the present invention has a linear thermal expansion coefficient between 12ppm / ℃ and 35ppm / ℃, the circuit board has the characteristic of high dimensional stability.

[0170] The fourth aspect of the present invention provides a gas barrier film composite film, which is the polyimide film provided by the first aspect of the present invention or includes the polyimide film provided by the first aspect of the present invention. Further, in one embodiment, the gas barrier composite film is a lining material for a hydrogen transport pipeline, and the polyimide film provided by the first aspect of the present invention is used as the lining material or a part of the lining material. Since the polyimide film provided by the first aspect has a H2 transmittance of ≤1.0×10 -15 mol·m / m 2 ·s·Pa characteristics, so the gas barrier film composite film has the characteristics of high gas barrier properties.

[0171] The fifth aspect of the present invention provides an insulating composite film, which includes the polyimide film provided by the first aspect of the present invention. Further, in one embodiment, the insulating composite film is an insulating layer of a high-voltage cable, and the polyimide film provided by the first aspect of the present invention is used as a part of the insulating layer. Since the polyimide film provided by the first aspect has a breakdown voltage of ≥30kV, the insulating composite film has the characteristic of high insulation.

[0172] Figure 1 A device for performing the method for preparing a polyimide film provided by the second aspect of the present invention. Figure 1 As shown, the device includes 101-a first extrusion die head, 102-a second extrusion die head, 103-a mixer, 104-a first heating driving roller, 105-a first heating driven roller, 106-a second heating driven roller, 107-a third heating driven roller, 108-a fourth heating driven roller, 109-a fifth heating driven roller, 110-a sixth heating driven roller, 111-a second heating driving roller, A-a first drying zone (hereinafter referred to as zone A), B-a second drying zone (hereinafter referred to as zone B), C-a third drying zone (hereinafter referred to as zone C), D-a fourth drying zone (hereinafter referred to as zone D), E-a fifth drying zone (hereinafter referred to as zone E), F-a sixth drying zone (hereinafter referred to as zone F), and G-a seventh drying zone (hereinafter referred to as zone G).

[0173] Among them, 101-the first extrusion die is used to cast the first resin solution to form a solution film; 103-the mixer is used to mix the chemical imidization agent, the second resin solution and the molecular weight reinforcement agent to obtain the second resin mixed solution and then enter 102-the second extrusion die, 102-the second extrusion die extrude the second resin mixed solution and perform at least one lamination-heating treatment on the initial A film layer.

[0174] 104-first heating driving roller, 105-first heating driven roller, 106-second heating driven roller, 107-third heating driven roller, 108-fourth heating driven roller, 109-fifth heating driven roller, 110-sixth heating driven roller, 111-second heating driving roller are moving structures with a steel belt attached to the outer surface, which can make the steel belt rotate counterclockwise around the above-mentioned moving structure.

[0175] A-first drying zone (hereinafter referred to as zone A), B-second drying zone (hereinafter referred to as zone B), C-third drying zone (hereinafter referred to as zone C), D-fourth drying zone (hereinafter referred to as zone D), E-fifth drying zone (hereinafter referred to as zone E), F-sixth drying zone (hereinafter referred to as zone F), G-seventh drying zone (hereinafter referred to as zone G). It is a heating plate with a heat source inside, which is arranged around the steel belt and is used to perform heating and drying treatment.

[0176] The process of using the above device for the production of polyimide film is as follows: 101-the first extrusion die extrudes the first resin solution onto the steel belt to form a solution film, A-the first drying zone and 104-the first heating drive roller, 105-the first heating driven roller, 106-the second heating driven roller are respectively located on the upper surface and the lower surface of the solution film, and the first heating and drying treatment is performed on it to obtain the initial A film layer, when the initial A film layer moves counterclockwise to 102-just below the second extrusion die, 102-the second extrusion die extrude the second resin mixed solution, and the solution film formed by the solution flow covers the upper surface of the initial A film layer, and moves to below B-the second drying zone, 107-the third heating driven roller, 108-the fourth heating driven roller for heating. The above process is to use the second resin mixed solution to perform a lamination-heating treatment on the initial A film layer to obtain an initial composite adhesive film.

[0177] The initial composite film moves counterclockwise, and the second heating and drying treatment is performed under C-the third drying zone, 109-the fifth heating driven roller, and 110-the sixth heating driven roller. Similarly, the sixth heating and drying treatment is performed above G-the seventh drying zone, 104-the first heating driving roller, 105-the first heating driven roller, and 106-the second heating driven roller to obtain the intermediate composite film. The intermediate composite film is longitudinally stretched at room temperature, transversely stretched within 150°C~600°C, and cooled to obtain a polyimide film.

[0178] The present invention also provides a standard for the solvent content and tensile strength of an intermediate composite film for producing a polyimide film. The solvent content and tensile strength of the intermediate composite film meet the standards shown in Table 1, and the intermediate composite film is subjected to biaxial stretching and high-temperature treatment to produce a polyimide film of corresponding thickness. Composite film solvent content = [(total weight of composite film - weight of composite film dried at high temperature) / weight of composite film dried at high temperature] × 100%; the weight of composite film dried at high temperature is the weight of the composite film after being dried at 450°C for 2 hours; the tensile strength of the intermediate composite film is obtained by testing with an Instron 68SC-05 universal tensile testing machine.

[0179]

[0180] The polyimide film and the preparation method thereof provided by the present invention are further introduced through various embodiments below.

[0181] Example 1

[0182] This embodiment uses the following method and Figure 1 The equipment shown below is used to prepare polyimide film:

[0183] 1) Preparation of the first resin solution

[0184] Under nitrogen protection, add 3139g DMF and 1046g THF to a 15L reactor; start stirring; weigh 1243g BAPP and 606g 3,4-ODA, add them to the reactor in sequence and stir at room temperature for 30min; weigh 3g calcium pyrophosphate and add it to the reactor; stir for 20min; weigh 1880g ODPA and slowly add it to the reactor; stir for 300min; obtain a first resin solution with a solid content of 47% and a viscosity of 1815P; store it in a freezer at -10°C for future use.

[0185] 2) Preparation of the second resin solution

[0186] Under nitrogen protection, add 10484g DMF to a 20L reactor; start stirring; weigh 1170g ODA and 632g PDA, add them to the reactor and stir at room temperature for 30min; weigh 3g calcium pyrophosphate and add them to the reactor; stir for 20min; weigh 1174g PMDA and 1514g s-BPDA and slowly add them to the reactor in sequence; stir for 300min; obtain a second polyamic acid resin solution with a solid content of 30% and a viscosity of 2005P; store it in a freezer at -10°C for future use.

[0187] 3) Preparation of double-layer polyimide composite membrane

[0188] ① Preparation of chemical imidization reagent: Under nitrogen protection, add 800 g DMF, 2198 g acetic anhydride, 1002 g 3-methylpyridine and 200 g triphenyl phosphate into a 5 L reactor in sequence and stir for 180 min for standby use.

[0189] ② Preparation of molecular weight reinforcing agent: Under nitrogen protection, add 1200g DMF and 600g 1,2,4,5-pyromellitic acid into a 2L reactor in sequence and stir at 60°C for 120min for standby use.

[0190] ③ Pump the first polyamic acid solution into the first extrusion die head and cast it onto the surface of the steel belt. The first layer of film runs along with the steel belt in the A zone and undergoes the first heating and drying treatment to obtain the initial A film layer;

[0191] The chemical imidization agent and molecular weight reinforcing agent in ① and ② and the second resin solution are quantitatively pumped into a mixer and fully mixed to obtain a second resin mixed solution, the second resin mixed solution is pumped into a second extrusion die head, the second resin mixed solution is cast onto the upper surface of the initial A film layer, and a heating treatment is performed in the B area to obtain an initial composite adhesive film with a two-layer structure (i.e., the initial A film layer is subjected to a lamination-heating treatment using the second resin mixed solution);

[0192] The initial composite film is subjected to the second drying treatment in zone C, the third drying treatment in zone D, the fourth drying treatment in zone E, the fifth drying treatment in zone F, and the sixth drying treatment in zone G as the steel belt runs, thereby obtaining an intermediate composite film with a certain solvent content and mechanical properties. The intermediate composite film is longitudinally stretched at room temperature, transversely stretched within 150°C to 600°C, and cooled to obtain a polyimide film with a thickness of 252 μm.

[0193] The quantitative relationship between the first resin solution, the second resin solution, the chemical imidization agent, and the molecular weight reinforcing agent is shown in Table 2:

[0194]

[0195] Specifically, in Example 1, the treatment time, air surface temperature (upper surface heating temperature) and steel strip surface temperature (lower surface heating temperature) of zone A (first heating and drying treatment), zone B (first lamination-heating treatment), zone C (second heating and drying treatment), zone D (third heating and drying treatment), zone E (fourth heating and drying treatment), zone F (fifth heating and drying treatment) and zone G (sixth heating and drying treatment) are shown in Table 3:

[0196]

[0197] Embodiment 2-8

[0198] Embodiments 2-8 are basically the same as Embodiment 1, except that the feeding flow rates of the first extrusion die head and the second extrusion die head are different. The specific feeding flow rate data are shown in Table 4:

[0199]

[0200] In Example 2-8, the treatment time, air surface temperature (upper surface heating temperature) and steel strip surface temperature (lower surface heating temperature) of Zone A (first heating and drying treatment), Zone B (first lamination-heating treatment), Zone C (second heating and drying treatment), Zone D (third heating and drying treatment), Zone E (fourth heating and drying treatment), Zone F (fifth heating and drying treatment) and Zone G (sixth heating and drying treatment) are shown in Table 5:

[0201]

[0202] Examples 9-10

[0203] In Examples 9-10, another device was used to prepare a polyimide film having a three-layer structure. Figure 1 The device is basically the same, except that the device further includes a third extrusion die head, which is located at the front end of zone C and the rear end of zone B (the front end is the running direction of the steel strip). Embodiments 9-10 are basically the same as embodiment 1, except that:

[0204] The chemical imidization agent and molecular weight reinforcing agent in ① and ② and the second resin solution are quantitatively pumped into a mixer and fully mixed to obtain a second resin mixed solution, and the second resin mixed solution is pumped into the second extrusion die and the third extrusion die respectively, and the second resin mixed solution extruded from the second extrusion die is cast onto the upper surface of the initial A film layer, and is heated in the B area. When the formed composite system runs to the junction of the B area and the C area, the second resin mixed solution extruded from the third extrusion die is cast onto the upper surface of the composite system, and is heated in the C area to obtain an initial composite adhesive film with a three-layer structure (that is, the initial A film layer is laminated and heated twice using the second resin mixed solution);

[0205] The initial composite film is subjected to the second drying treatment in zone D, the third drying treatment in zone E, the fourth drying treatment in zone F, and the fifth drying treatment in zone G as the steel belt runs, thereby obtaining an intermediate composite film. The intermediate composite film is longitudinally stretched at room temperature, transversely stretched within 150°C to 600°C, and cooled to obtain a three-layer polyimide film.

[0206] The specific feed flow data of each extrusion die head are shown in Table 6:

[0207]

[0208] In Examples 9-10, the treatment time, air surface temperature (upper surface heating temperature) and steel strip surface temperature (lower surface heating temperature) of Zone A (first heating and drying treatment), Zone B (first lamination-heating treatment), Zone C (second lamination-heating treatment), Zone D (second heating and drying treatment), Zone E (third heating and drying treatment), Zone F (fourth heating and drying treatment) and Zone G (fifth heating and drying treatment) are shown in Table 7:

[0209]

[0210] Embodiment 11

[0211] This embodiment is basically the same as embodiment 2, except that the preparation process of the first resin solution is as follows:

[0212] Under nitrogen protection, add 4000g DMAc and 2000g butanone to a 15L reactor; start stirring; weigh 1006g GAPDS and 495g DAT, add them to the reactor and stir at room temperature for 30min; weigh 4g calcium pyrophosphate and add them to the reactor; stir for 20min; weigh 1306g BTDA and 1192g a-BPDA and slowly add them to the reactor in sequence; stir for 300min; obtain a first polyamic acid resin solution with a solid content of 40% and a viscosity of 1903P; store it in a frozen state at -10°C for future use.

[0213] Example 12

[0214] This embodiment is basically the same as embodiment 2, except that the preparation process of the second resin solution is as follows:

[0215] Under nitrogen protection, add 10080g DMF to a 20L reactor; start stirring; weigh 1638g ODA and 380g PDA, add them to the reactor and stir at room temperature for 30min; weigh 4.5g calcium pyrophosphate and add them to the reactor; stir for 20min; weigh 2296g PMDA and slowly add them to the reactor in sequence; stir for 300min; obtain a second polyamic acid resin solution with a solid content of 30% and a viscosity of 2536P; store it in a freezer at -10°C for future use.

[0216] Example 13

[0217] This embodiment is basically the same as embodiment 2, except that the preparation process of the first resin solution is as follows:

[0218] Under nitrogen protection, add 3669g DMAc and 1223g butanone to a 15L reactor; start stirring; weigh 1006g GAPDS and 495g DAT, add them to the reactor and stir at room temperature for 30min; weigh 4g calcium pyrophosphate and add them to the reactor; stir for 20min; weigh 1306g BTDA and 1192g a-BPDA and slowly add them to the reactor in sequence; stir for 300min; obtain a first polyamic acid resin solution with a solid content of 45% and a viscosity of 1822P; store it in a freezer at -10°C for future use.

[0219] Embodiment 14

[0220] This embodiment is basically the same as embodiment 2, except that the preparation process of the second resin solution is as follows:

[0221] Under nitrogen protection, add 8070g DMF to a 20L reactor; start stirring; weigh 1638g ODA and 380g PDA, add them to the reactor and stir at room temperature for 30min; weigh 4.5g calcium pyrophosphate and add them to the reactor; stir for 20min; weigh 2246g PMDA and slowly add them to the reactor in sequence; stir for 300min; obtain a second polyamic acid resin solution with a solid content of 34.5% and a viscosity of 2337P; store it in a freezer at -10°C for future use.

[0222] Embodiment 15

[0223] This embodiment is basically the same as embodiment 2, except that the configuration of the chemical imidization reagent is as follows:

[0224] Under nitrogen protection, 800 g of DMF, 2198 g of acetic anhydride, 1390 g of isoquinoline and 200 g of triphenyl phosphate were added to a 5 L reactor in sequence and stirred for 180 min for standby use.

[0225] Example 16

[0226] This embodiment is basically the same as embodiment 2, except that the configuration of the molecular weight reinforcing agent is as follows:

[0227] Under nitrogen protection, 1200 g of DMF and 600 g of 1,2,3,4-cyclobutanetetracarboxylic acid were added to a 2 L reactor in sequence and stirred at room temperature for 120 min for standby use.

[0228] Comparative Example 1

[0229] This comparative example adopts the second resin mixed solution used in Example 2 (including the second resin solution, the chemical imidization agent, and the molecular weight reinforcing agent solution) to prepare an ultra-thick polyimide film with a single-layer structure, that is, the second resin solution, the chemical imidization agent, and the molecular weight reinforcing agent solution are quantitatively pumped into a mixer for mixing and pumped into a second extrusion die, and the rest is the same as Example 2.

[0230] Comparative Example 2

[0231] The first resin solution in Example 2 is used to prepare a single-layer ultra-thick polyimide film, that is, the first polyamic acid resin solution is pumped into the first extrusion die head, and the rest is the same as in Example 2.

[0232] Comparative Example 3

[0233] The second resin solution, chemical imidization agent, molecular weight reinforcing agent and first resin solution of Example 2 are used to prepare the A film layer and the B film layer respectively, and the rest is the same as Example 2.

[0234] Comparative Example 4

[0235] 1) Preparation of the first polyamic acid resin solution

[0236] Under nitrogen protection, 4767g DMF and 1559g THF were added to a 15L reactor; stirring was started; 622g BAPP was weighed and added to the reactor and stirred at room temperature for 30min; 1.5g calcium pyrophosphate was weighed and added to the reactor; stirring was carried out for 20min; 469g ODPA and 303g 3,4-ODA were weighed and slowly added to the reactor in sequence; stirring was carried out for 300min; a first polyamic acid resin solution with a solid content of 18% and a viscosity of 2239P was obtained; the solution was frozen and stored at -10°C for future use.

[0237] 2) Preparation of the second polyamic acid resin solution

[0238] Under nitrogen protection, add 10972g DMF to a 20L reactor; start stirring; weigh 585g ODA and 316g PDA, add them to the reactor and stir at room temperature for 30min; weigh 1.5g calcium pyrophosphate and add them to the reactor; stir for 20min; weigh 637g PMDA and 869g s-BPDA and slowly add them to the reactor in sequence; stir for 300min; obtain a second polyamic acid resin solution with a solid content of 18% and a viscosity of 1706P; store it in a freezer at -10°C for future use.

[0239] The rest is the same as in Example 2. The prepared two-layer composite film has a solvent content of 561% and a tensile strength of 21 MPa. The film is separated from the fixture during high-temperature treatment, and a polyimide film with a thickness of 300 μm cannot be stably produced.

[0240] Comparative Example 5

[0241] This comparative example is basically the same as Example 2, except that the treatment time, air surface temperature (upper surface heating temperature) and steel strip surface temperature (lower surface heating temperature) of Zone A (first heating and drying treatment), Zone B (first lamination-heating treatment), Zone C (second heating and drying treatment), Zone D (third heating and drying treatment), Zone E (fourth heating and drying treatment), Zone F (fifth heating and drying treatment) and Zone G (sixth heating and drying treatment) are shown in Table 8:

[0242]

[0243] Comparative Example 6

[0244] This comparative example is basically the same as Example 2, except that the treatment time, air surface temperature (upper surface heating temperature) and steel strip surface temperature (lower surface heating temperature) of Zone A (first heating and drying treatment), Zone B (first lamination-heating treatment), Zone C (second heating and drying treatment), Zone D (third heating and drying treatment), Zone E (fourth heating and drying treatment), Zone F (fifth heating and drying treatment) and Zone G (sixth heating and drying treatment) are as shown in Table 9:

[0245]

[0246] Test example

[0247] The solvent content and tensile strength of the films in the above embodiments and comparative examples as well as the thickness of the produced ultra-thick polyimide films are statistically analyzed, and the data are shown in Table 10.

[0248]

[0249] in:

[0250] 1) During the preparation of Comparative Example 1, the film shrank and tore during the drying process, and production could not be performed. This indicates that a single-layer polyimide film cannot be produced using only the second resin mixed solution;

[0251] 2) During the preparation of Comparative Example 2, the adhesive film adhered to the steel belt after drying and was difficult to peel off, and the adhesive film tore under tension, making it impossible to produce. This shows that a single-layer polyimide film cannot be produced using only the first resin solution;

[0252] 3) During the preparation of Comparative Example 3, the film shrank and tore during the drying process, and production could not be achieved. This indicates that when the corresponding relationship between the first resin solution and the second resin solution and the A film layer and the B film layer is swapped, a polyimide film cannot be produced;

[0253] 4) The solvent content of the two-layer intermediate composite film prepared in Comparative Example 4 was 561%, the tensile strength was 21 MPa, and the film was separated from the fixture during high-temperature treatment, and a polyimide film with a thickness of 300 μm could not be stably produced. This shows that it is difficult to produce a polyimide film product when the solvent content of the intermediate composite film is too high;

[0254] 5) The intermediate composite film obtained in Comparative Example 5 has a solvent content of 372% and a tensile strength of 36 MPa. During high-temperature treatment, the film detaches from the fixture and a polyimide film with a thickness of 300 μm cannot be stably produced. This shows that it is difficult to produce a polyimide film product when the solvent content of the intermediate composite film is too high;

[0255] 6) During the drying process of the film of Comparative Example 6, a large amount of solvent dripped back to the surface to form streaks. The solvent content of the prepared film was 167%, the tensile strength was 72MPa, and a polyimide film with a thickness of 295μm was produced after biaxial stretching and high temperature treatment. This shows that when the air surface temperature is too low, there are streaks on the surface formed by a large amount of solvent dripping back to the surface.

[0256] 7) In addition, the low heating temperature of the air side and the large difference between the heating temperature of the steel strip side will not only cause the solvent to drip back to the surface of the film layer to form defects; it will also cause the film to be insufficiently dried, the solvent content of the obtained product is high, and the comprehensive performance of the final prepared composite film is low.

[0257] The structure and performance statistics of the ultra-thick polyimide film in the above embodiments are shown in Table 11, and the measurement method is as follows:

[0258] Thickness measurement method: using CHY-CA mechanical contact thickness gauge produced by China Saicheng Instruments;

[0259] CTE measurement method: measured using the TMA450 static thermomechanical analyzer from TA, USA, with a heating rate of 3°C / min;

[0260] Breakdown voltage measurement method: measured using SDJ-150KV thin film voltage breakdown tester from China Guanheng Precision Instruments, with a voltage rise rate of 500V / s;

[0261] H2 permeability measurement method: using SMT-275 membrane separation test analyzer from China Sike Testing Technology, with a hydrogen intake rate of 50ml / min;

[0262] Surface roughness RZ measurement method: using Marsurf VD140 280 profile roughness measuring instrument from Marl, Germany;

[0263] Glass transition temperature Tg measurement method: using DMA303 from NETZSCH, Germany, with a heating rate of 3°C / min;

[0264] Method for measuring the number of micropores: A German Zeiss GeminiSEM 360 scanning electron microscope was used to detect the cross section of the polyimide film sample and to count the number of micropores with a size greater than 0.1 mm.

[0265] Density measurement method: DH-300 thin film rapid density meter produced by China Hongtuo Instruments was used for detection.

[0266]

[0267] Where: CTE: coefficient of linear thermal expansion;

[0268] BV: breakdown voltage;

[0269] Rz: surface roughness;

[0270] Tg: glass transition temperature;

[0271] ρ: density.

[0272] It can be seen from Table 11 that the polyimide films prepared in various embodiments of the present invention have the characteristics of large thickness, low thermal expansion, high pressure resistance and low gas permeability.

[0273] In the description of the embodiments of the present application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, or it can be an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0274] The terms "first", "second", "third", "fourth", etc. (if any) in the specification and claims of the present application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein, for example. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0275] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some or all of the technical features can be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the technical solutions of the embodiments of the present invention.

Claims

1. A polyimide film, characterized in that: The polyimide film has a thickness greater than or equal to 250 μm and includes a film layer A and at least one film layer B that are in contact with each other; The surface roughness of the A film layer is Rz≤1.0 μm; The number of micropores with a size greater than 0.1 mm in the B film layer is ≤ 1 / ㎡, and the density of the B film layer is ≥ 1.45 g / cm 3 , surface roughness Rz ≥ 1.2 μm; The preparation of the polyimide film comprises the following steps: 1) mixing a first aromatic dianhydride, a first aromatic diamine, a low boiling point solvent, a high boiling point solvent, and a filler, and causing the first aromatic dianhydride and the first aromatic diamine to undergo a polycondensation reaction to obtain a first resin solution; 2) mixing a second aromatic dianhydride, a second aromatic diamine, a high boiling point solvent, and a filler, and causing the second aromatic dianhydride and the second aromatic diamine to undergo a polycondensation reaction to obtain a second resin solution; 3) performing a first heating and drying treatment on the solution film formed by casting the first resin solution to obtain an initial A film layer; 4) mixing the second resin solution with a chemical imidization agent and a molecular weight reinforcing agent to obtain a second resin mixed solution; Using the second resin mixed solution to perform at least one lamination-heating treatment on the initial A film layer to obtain an initial composite adhesive film; 5) performing at least one heating and drying treatment on the initial composite film to obtain an intermediate composite film; 6) subjecting the intermediate composite film to high temperature heating and biaxial stretching treatment to obtain the polyimide film; The treatment temperature of the first heating and drying treatment is 50°C to 120°C, and the treatment time is 2min to 10min; The lamination-heating treatment includes attaching the second resin mixed solution to the surface direction of one side of the initial A film layer, and performing a heating treatment at a temperature of 60° C. to 150° C. for a time of 5 min to 15 min; The heating and drying treatment of the initial composite film is performed at a temperature of 50°C to 180°C and a treatment time of 18min to 60min; The first aromatic dianhydride is selected from at least one of pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4-biphenyltetracarboxylic dianhydride, 4,4'-biphenyl ether dianhydride, 3,4,3',4'-triphenyl diether dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]malonic dianhydride, 2,2-diphenylpropane-3,4,3',4'-tetracarboxylic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-diphenyl sulfone tetracarboxylic dianhydride, and p-phenylene-bis(triphenyl)phthalate dianhydride; The first aromatic diamine is selected from at least one of 4,4'-diaminodiphenyl ether, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminodiphenylmethane, 2,2-bis(4-aminophenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 2,4-diaminotoluene, and 1,3-bis(aminopropyl)tetramethyldisiloxane; The second aromatic dianhydride is selected from at least one of pyromellitic dianhydride and 3,3,4,4'-biphenyltetracarboxylic dianhydride; The second aromatic diamine is selected from at least one of 4,4'-diaminodiphenyl ether and 1,4-phenylenediamine; The solid content of the first resin solution is 10%-50%; The solid content of the second resin solution is 10%-35%; The low boiling point solvent is selected from at least one of acetone, butanone, toluene, ethyl acetate, tetrahydrofuran and chloroform; The high boiling point solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone; The filler is selected from at least one of calcium carbonate, calcium phosphate, calcium pyrophosphate, calcium hydrogen phosphate, silicon carbide, carbon nanotubes, graphene, carbon black, silicon dioxide, and titanium dioxide; The chemical imidization reagent includes a dehydrating agent, a catalyst, an imidization solvent, and an auxiliary agent; The dehydrating agent is selected from at least one of acetic anhydride, trifluoroacetic anhydride, benzoic anhydride, acetyl chloride and thionyl chloride; The catalyst is selected from at least one of quinoline, isoquinoline, pyridine, 3-methylpyridine, triethylamine, and N-methylimidazole; The imidization solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone; The auxiliary agent is selected from at least one of tricresyl phosphate, triphenyl phosphate, toluene diphenyl phosphate, and trioctyl trimellitate; The molecular weight reinforcing agent is selected from at least one of 1,2,4,5-pyromellitic acid, 3,3',4,4'-biphenyltetracarboxylic acid, tetrahydrofuran-2,3,4,5-tetracarboxylic acid, cyclohexane-1,2,4,5-tetracarboxylic acid, 1,2,3,4-cyclobutanetetracarboxylic acid, terephthalic acid, isophthalic acid, and terephthaloyl chloride; The heating temperature of the high temperature heating and biaxial stretching treatment in step 6) is 150°C to 600°C.

2. The polyimide film according to claim 1, characterized in that The linear thermal expansion coefficient of the polyimide film is 12ppm / ℃~35ppm / ℃, the breakdown voltage is ≥30kV, and the H2 transmittance is ≤1.0×10 -15 mol·m / m 2 ·s·Pa, the glass transition temperature of the polyimide in the A film layer is 180°C~300°C.

3. The polyimide film according to claim 1, characterized in that The thickness of the A film layer accounts for 20%-50% of the total thickness of the polyimide film.

4. The polyimide film according to claim 1, characterized in that In step 1), the molar ratio of the first aromatic dianhydride to the first aromatic diamine is 0.99:1 to 1.05:1; and / or, The molar ratio of the second aromatic dianhydride to the second aromatic diamine is 0.8:1 to 0.995:

1.

5. The polyimide film according to claim 1, characterized in that The solid content of the first resin solution is 30%-40%; and / or, The solid content of the second resin solution is 25%-35%.

6. The polyimide film according to claim 1, characterized in that The mass of the chemical imidization agent is 1%-30% of the mass of the second resin solution; and / or, The molar ratio of the dehydrating agent to the catalyst in the chemical imidization reagent is 1:2-5:1; the mass fraction of the solvent is 10%-40%; the mass fraction of the auxiliary agent is 1%-10%; and / or, The mass of the filler is 0.05% to 5% of the sum of the mass of the aromatic diamine and the aromatic dianhydride.

7. The polyimide film according to claim 1, characterized in that: The amount of the molecular weight enhancer is equal to the difference between the amounts of the second aromatic diamine and the second aromatic dianhydride.

8. The polyimide film according to claim 1, characterized in that: In step 5), the heating and drying treatment includes heating the upper surface and the lower surface of the initial composite film respectively, wherein the heating temperature of the upper surface is 50°C to 150°C, and the heating temperature of the lower surface is 80°C to 180°C.

9. The polyimide film according to claim 1, characterized in that: In step 5), the heating and drying treatment of the initial composite adhesive film includes a second heating and drying treatment, a third heating and drying treatment, a fourth heating and drying treatment, a fifth heating and drying treatment, and a sixth heating and drying treatment performed in sequence; The upper surface heating temperature of the second heating and drying treatment is 80°C to 120°C, the lower surface heating temperature is 120°C to 150°C, and the treatment time is 5min to 15min; The third heating and drying treatment has an upper surface heating temperature of 90°C to 135°C, a lower surface heating temperature of 135°C to 180°C, and a treatment time of 1min to 8min; The fourth heating and drying treatment has an upper surface heating temperature of 80°C to 120°C, a lower surface heating temperature of 120°C to 150°C, and a treatment time of 5min to 15min; The fifth heating and drying treatment has an upper surface heating temperature of 60°C to 120°C, a lower surface heating temperature of 120°C to 150°C, and a treatment time of 5min to 15min; The upper surface heating temperature of the sixth heating and drying treatment is 50°C to 100°C, the lower surface heating temperature is 100°C to 120°C, and the treatment time is 2min to 10min.

10. The polyimide film according to claim 1, characterized in that: In the stacking-heating treatment, the upper surface heating temperature of the heating treatment is 60°C to 120°C, and the lower surface heating temperature is 120°C to 180°C.

11. A circuit board, characterized in that: The invention comprises the polyimide film according to any one of claims 1 to 10.

12. A gas barrier composite film, characterized in that: The invention comprises the polyimide film according to any one of claims 1 to 10.

13. An insulating composite film, characterized in that: The invention comprises the polyimide film according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Preparation apparatus and preparation method of polyimide thick membrane or polyimide ultrathick membrane

    CN108527745A

  • An ultra-thick polyimide film, its preparation method, and graphite sheets.

    CN110423467B

  • Ultra-thick graphite heat-conducting film as well as preparation method and application thereof

    CN113788478A

  • Anti-condensation temperature-control fire extinguishing system for polyimide film production

    CN217654241U

  • Thick polyimide film and method for manufacturing same

    US20220152912A1